Еstimation of randomity of generators of keys of the crypto system - Jenaliyev, M.T.; Nurtazin, А.Т.; Khisamiev, Z.G. (KSU Publ., 2018)
The aim of the study is to develop an algorithm for constructing an integer random variable representing random components of the keys of the RSA cryptosystem, and determining the table for the distribution of its probabilities. The constructed random variable can be used to estimate the hypothesis that a given generator generates its values with the same probability with which a random variable takes these values. A hypothesis testing algorithm is provided, which is accompanied by a calculation table for a uniformly distributed random variable that takes primes from a given half-open interval.
Криптожүйе кiлттерi генераторларының кездейсоқ қасиетiн бағалау
Оценка свойства случайности генераторов ключей криптосистемы
Keywords: RSA-cipher; keys; random variable; prime number; probability distribution